PENGARUH APLIKASI BEBERAPA PUPUK SULFUR TERHADAP RESIDU, SERAPAN, SERTA PRODUKSI TANAMAN JAGUNG DI MOLLISOL JONGGOL, BOGOR, JAWA BARAT - Ayu Aisyah; I Wayan Suastika; Retno Suntari (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2015)
Mollisols are soils with good fertility but they have high base saturation and pH that affect the availability of sulfur. Sulfur is a secondary macronutrient that plant needs for the establishment and quality improvement of grain. The purposes of this study were to determine the effect of different sulfur fertilizers on criteria of S in the soil and S uptake of maize and understand the correlation between S uptake from some sulfur fertilizer and maize production in a Mollisol of Jonggol, Bogor, West Java. Materials used in this field study were a composite sample of Mollisols at a depth of 0-20 cm, ZA fertilizer, elemental sulfur, granulated sulfur and maize seeds. The study used completely randomized designwith 6 treatments and 3 replications. Results of this study showed that ZA fertilizer application at a dose of 60 kg S ha-1 resulted in the highest S residue 26.58 ppm and all application of sulfur fertilizer changed the criteria of S in the soil from very low to low. Some sulfur application were not significant to S-uptake by plant and grain but the highest value contained in the application of granulated sulfur at a dose of 150% S, respectively 3.42 and 1.76 g plant-1. S uptake by plant and grain was not correlated to the production of maize in the form of dry weight of maize, grain weight per plant, weight of 100 grains, and the number of grain per cob